Intuição e construção matemática na Crítica da razão pura: uma análise das interpretações de Parsons e Hintikka - Oliveira, Danilo Fernando Miner de (2020)
The subject of this investigation is the mathematical construction in Kant and its necessary link with the concept of intuition (Anschauung). It is at this point that several criticisms arise about the real foundation of this science in the Critique of pure reason, especially after Kant presents new elements, in different parts of the work, about the construction of concepts in mathematics. It is about this supposed mismatch that celebrated thinkers such as Jakko Hintikka and Charles Parsons disagree about the real meaning of the term intuition (Anschauung) and propose divergent re-readings about this reasoning, accusing Kant of engaging in a conceptual mismatch that weakens his theses on the mathematical foundation through the characteristics of singularity and immediacy attributed to the forms of intuition, that is, space and time. The purpose of this thesis is to analyze the main elements of mathematical grounding in the constitution of a priori synthetic judgments, to purify the criticisms made of this grounding, to investigate whether the intellectual mismatch, which Kant is accused of, is plausible in the light of a thorough examination of his claims mathematical theses and their transcendental idealism.